2022
DOI: 10.1063/5.0074010
|View full text |Cite
|
Sign up to set email alerts
|

On the polarity determination and polarity inversion in nitrogen-polar group III-nitride layers grown on SiC

Abstract: Note: This paper is part of the Special Topic on Wide Bandgap Semiconductor Materials and Devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Furthermore, it is essential to point out that for both the initial AlN layers are dominantly N-polar. This is the key point why LT AlN NLs can be completely etched away at the macroscale using KOH . The observed IDBs are similar to the Al 9 O 3 N 7 structures reported by Asaka et al and Stolyarchuk et al We also note that a simple cross-section overlap of adjacent N-polar and Al-polar lattices will result in the same appeared structure (see Figure S2 in the Supporting Information for comparisons of simulated ADF STEM images of different lattice overlap scenarios).…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Furthermore, it is essential to point out that for both the initial AlN layers are dominantly N-polar. This is the key point why LT AlN NLs can be completely etched away at the macroscale using KOH . The observed IDBs are similar to the Al 9 O 3 N 7 structures reported by Asaka et al and Stolyarchuk et al We also note that a simple cross-section overlap of adjacent N-polar and Al-polar lattices will result in the same appeared structure (see Figure S2 in the Supporting Information for comparisons of simulated ADF STEM images of different lattice overlap scenarios).…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, HR-XRD measurements combined with KOH etching indicate that the LT and HT AlN NLs are all N-polar on a macroscale, as evidenced by the disappearance of the AlN 0002 peak upon KOH etching (additional information on polarity determination of samples before and after KOH etching from HR-XRD can be found in the Supporting Information ). Recently, we have shown that KOH etching may provide an inconclusive polarity assignment in the case of mix-polarity AlN as Al-polar domains may be under- or overetched through adjacent N-polar pyramid domains and thus may remain undetected . Therefore, cross-sectional atomically resolved ADF STEM is used to determine the polarity by following the stacking order of Al and N atom positions along the growth direction.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations